PRAKTIK PENYALURAN TENAGA KERJA INDONESIA (TKI) ILEGAL KE LUAR NEGERI DI KOTA SEMARANG - Nungky Risanti Pusporini; Fitriyah .; yuwanto . (Journal of Politic and Government Studies, 2018)
One of the employment problems in Indonesia is the lack of employment that is not proportional to the number of workers, recruitment and Indonesia labor dispensing mechanisms to the welfare issue. The focus of this study is the Indonesian Migrant Workers distribution, which is about the practice of migrant workers abroad illegal distribution in the Semarang city In this research, the researcher raised 3 formulation problems that is how the illegal distribution practice of labor migrants abroad in Semarang City, what factors causing the illegal distribution of labor migrants abroad, and how Semarang City government efforts in combating illegal migrant workers abroad . The purpose of this research is to explain the illegal distribution practice of labor migrants abroad in Semarang City, explaining the factors that caused the illegal distribution of labor migrants abroad in Semarang City, and explained the efforts of Semarang City government in combating illegal migrant workers abroad.The research was conducted by using descriptive qualitative method. The data collection techniques were conducted with interviews and documentation. Informants in this research are illegal migrant workers, legal Indonesian Migrant Workers (TKI) dealers, former illegal workers, former legal workers, and Head of Labor and Transmigration department (Disnakertrans) Semarang City.The result of the research shows that the illegal distribution practice of labor migrants abroad in Semarang City conducted by labor brokers or tekong. The targets of illegal migrant workers to be sent abroad are women and those with insufficient knowledge, low education, making it easier to tempt the big salaries lure. The factor is that prospective migrant workers want to work abroad easily, practically and3cheaply. The Government seeks to eradicate by forming an illegal Task Force team consisting of the labor, police, immigration service, labor inspectors’ elements, and airport authorities or local port authorities.This study concludes the disbursement of Illegal Indonesian Workers due to internal factors and external factors. As with economic factors, the study also found differences in legal and illegal treatment, which are legally protected. Since this is an aberration, the government should provide strengthening for the task force and add the dangers’ socialization, the risk of becoming an illegal labor migrant. Provides socialization of the correct procedures for working abroad, since illegally can harm the prospective workforce directly and the state indirectly.Keywords: Abroad Workers Distribution, Legal Indonesian Migrant Workers (TKI), Illegal Indonesian Migrant Workers (TKI), Migrant workers.